2020
DOI: 10.22454/fammed.2020.314090
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Direct Observation of Medical Students With Patient-Centered Care for Obesity

Abstract: Background and Objectives: Teaching medical students patient-centered approaches to weight loss counseling occurs in myriad ways. We examined lectures and direct faculty observation to see which was associated with better patient-centered care in medical students, measured by both self-perception and independent observer evaluation. Methods: Third- and fourth-year students attending one medical school were surveyed regarding their education in (1) weight loss and health behavior counseling, (2) obesity stigma,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…We performed a literature review to investigate which teaching tools have been shown to be effective in prior studies. 5,[9][10][11][12][13][14][15][16][17][18][19] Additionally, the teaching tools needed to be convenient to perform in the hospital setting and be in accordance with the guidelines of our hospital and college. The six teaching tools used by the faculty included:…”
Section: Teaching Methodsmentioning
confidence: 99%
“…We performed a literature review to investigate which teaching tools have been shown to be effective in prior studies. 5,[9][10][11][12][13][14][15][16][17][18][19] Additionally, the teaching tools needed to be convenient to perform in the hospital setting and be in accordance with the guidelines of our hospital and college. The six teaching tools used by the faculty included:…”
Section: Teaching Methodsmentioning
confidence: 99%
“…Many practitioners, patients, and observers have witnessed how the craft of generalism, 64 , 72 , 84 as manifested in primary care, influences the health of real people over time in ways that collectively lead to improved population health. Complex system models 85 , 86 and theories 87 , 88 can help to convey how health emerges at the level of the person and population by paying attention to related factors on the ground, but many times, that complexity is most easily shared through stories.…”
Section: Interacting Mechanisms: How Primary Care Work To Advance Per...mentioning
confidence: 99%
“…Based upon this notion and a significant number of reports in the literature about the importance and superiority of direct observation, I have changed what I do when evaluating residents. [3][4][5] On an inpatient service, I minimize all other commitments so that I am present on the ward for almost the entire day and evening. This allows me to see almost all patients on admission with the residents and to be present when acute events occur.…”
Section: Journal Of Medical Education and Curricular Developmentmentioning
confidence: 99%
“…Encounter cards and checklists have also been developed to aid in direct observation. 5,6 It is a privilege to be a faculty preceptor. My experience suggests that being present in the training space promotes best practices in all competencies.…”
Section: Journal Of Medical Education and Curricular Developmentmentioning
confidence: 99%